FITUR BAHASA PEREMPUAN DAN LAKI-LAKI DALAM GELAR WICARA MATA NAJWA EKSKLUSIF 2024 - Alfaris, Reza Salman; Darmayanti, Nani; Adji, Muhamad (Universitas Sultan Ageng Tirtayasa, 2025)
Based on the theory of Lakoff and Coates, this study aims to identify the types of language features based on female and male genders. In addition, this study also aims to describe the functions of language features based on female and male gender spoken by speakers at the Mata Najwa Exclusive in 2024. The research methods used are descriptive qualitative methods. The object of this research includes variables of words, phrases, clauses, and sentences that are identified as female language features and male language features. The results of the study showed that there were 1,397 speeches containing female and male language features. A total of 924 speeches were women's language features. Then, as many as 473 of them are speeches that are included in the features of male language. In addition, it was also found that each feature of female and male language has its own function according to the context of the speech.